2018
DOI: 10.1051/shsconf/20185001082
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Method in Interdisciplinary Terminological Landscape Research of Digital Economy

Abstract: The science in the digital age focuses on interdisciplinary research as the main driver of the development. Modern studies of semantic and thematic contexts taken from the digital scientific resources are important for tasks of information technology use in science, education, management and business. As a rule, interdisciplinary research emerges in response to the trends in social and economic development. Socio-political and cultural environment has also a great influence on the introduction of new terminolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The aim of the research of the synthetic measure is to measure complex groups of variables [53] that are determined to describe the state from several perspectives [54]. This method has recently gained popularity, especially in applied sciences such as economics.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of the research of the synthetic measure is to measure complex groups of variables [53] that are determined to describe the state from several perspectives [54]. This method has recently gained popularity, especially in applied sciences such as economics.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it allows, through explication and mapping, forming collections of fragments (thematic contexts) that are thematically relevant to the interdisciplinary direction. In the frames of the research, the theoretical and practical results of applying science-research methods for extracting, processing and analyzing contextual knowledge have been analyzed [Kononova O., Prokudin D., 2018]. Thus, the research agenda consists in identifying semantic groups and contexts, revealing patterns and building trends that reflect the development dynamics of topics in the scientific and public discourse.…”
Section: Methodsmentioning
confidence: 99%
“…The theoretical basis of the study is discourse analysis, advanced content analysis with the subsequent explication of selected contexts (synthetic method), expert, and comparative analysis. The authors' automated technique of extraction and explication of contextual knowledge (a form of an interpretation of the texts and explication of meanings through contexts obtained as a result of search queries), using a hybrid query for the analysis of contexts from textual modality information resources, has been applied [Kononova, Prokudin, 2018].…”
Section: Gamification In Russian and English Discoursementioning
confidence: 99%
“…The purpose of the study presented in this paper is to identify the terminological landscape of gamification domain with usage of retrieval systems and semantic tools. A comparative analysis of the terminological landscape on the base of Synthetic Method presented by the authors [Kononova, Prokudin, 2018] has revealed the contexts of using gamification in the urban environment development and the modern city management. It has also highlighted promising proposals and practices on gamification using in the development of the city information space and formed the terminological base and thesaurus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation